Navigating Educational Frontiers: Students' Perspectives on Interdisciplinary Teacher Collaboration in ESP Classroom - Rahmiatin, Titin; Ilham, Muhammad (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2024)
The purpose of this study was to investigate students' perceptions of interdisciplinary teacher collaboration (ITC) in ESP classes and to explore the challenges and problems students face during the implementation of ITC. The study involved 38 students from three non-English majors (Department of Agriculture, Department of Fisheries, and Department of Politics and Science). Quantitative and qualitative methods were employed, with the quantitative method used to investigate students' perception of ITC through team teaching and teachers' teaching methods in the ESP classroom. The qualitative method was used to explore the challenges and problems students faced during the implementation of ITC in the ESP context. Data was collected through a questionnaire on Google Forms and individual interviews with 12 students. The results showed that students had a positive reaction to the implementation of ITC, particularly in the areas of team teaching and teachers' teaching methods. However, challenges related to pronunciation, listening, misinterpretation, confidence, writing, grammar, and speaking were identified during the implementation of ITC.